2022
DOI: 10.3390/su14095143
|View full text |Cite
|
Sign up to set email alerts
|

Study on Crack Classification Criterion and Failure Evaluation Index of Red Sandstone Based on Acoustic Emission Parameter Analysis

Abstract: The acoustic emission (AE) characteristics of rock during loading can reflect the law of crack propagation and evolution in the rock. In order to study the fracture mode in the process of rock fracture, the AE characteristics and crack types of red sandstone during fracture were investigated by conducting Brazilian indirect tensile tests (BITT), direct shear tests (DST), and uniaxial compression tests (UCT). The evolution law of AE event rate, RA and AF values, and the distribution law of RA–AF data of red san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Many studies have shown that the number of shear rupture activities will increase significantly when the specimen approaches the destabilization stage in the experimental processes of the rock triaxial compression test, cubic compression test with cracks, strain-type rock explosion, and the specimen damage process [17][18][19][20][21][22][23][24][25][26][27][28][29]. However, tensile fracture is the main failure mode in concrete bending and barite direct tensile tests.…”
Section: Ae Energy Parameters For Pipeline Damage Identificationmentioning
confidence: 99%
“…Many studies have shown that the number of shear rupture activities will increase significantly when the specimen approaches the destabilization stage in the experimental processes of the rock triaxial compression test, cubic compression test with cracks, strain-type rock explosion, and the specimen damage process [17][18][19][20][21][22][23][24][25][26][27][28][29]. However, tensile fracture is the main failure mode in concrete bending and barite direct tensile tests.…”
Section: Ae Energy Parameters For Pipeline Damage Identificationmentioning
confidence: 99%
“…To study the fracture patterns during rock fracture, Li et al [34] investigated the acoustic emission characteristics and crack types of red sandstone during fracture by Brazilian indirect tensile tests (BITT), direct shear tests (DST), and uniaxial compression tests (UCT). They also discussed a relatively objective dividing line for tensile and shear crack classification and applied the dividing line to the analysis of the fracture source evolution and the damage precursor.…”
Section: Guarantee For Mining Production Safetymentioning
confidence: 99%
“…Luo [30] studied the patterns of cumulative acoustic emission counts and amplitudes during the failure process of red sandstone under various shear angle conditions. Li [31] conducted a comparative analysis of the differences in acoustic emission count variations during the failure process of red sandstone under three different loading conditions: uniaxial compression, Brazilian splitting, and shear. Li [32] compared the differences in acoustic emission B-values and peak frequency variations during the failure process of rocks from different geological formations, such as granite, sandstone, and marble, within the same region under Brazilian splitting loading conditions.…”
Section: Introductionmentioning
confidence: 99%